Analysis of Factors Affecting Employee Performance at Public Health Center - Khatob, Khatob; Gustina, Erna; Rahutami, Syntia (Universitas Islam Jember, 2024)
Performance plays a crucial role in all types of organizations, both public and private sectors. It can be defined as the outcome of tasks executed in line with assigned responsibilities, which is clearly reflected in the results or output produced (Pranogyo et al., 2021). The quality of services provided by employees plays a significant role in shaping the public's perception of healthcare services. Patients' experiences are often shared with family and close friends, creating either a positive or negative impression of the health center (Argaheni et al., 2022). This study aims to identify factors affecting employee performance at Puskesmas Sumber Harum in 2024. The research uses a quantitative approach with a cross-sectional design, classified as observational research. The study involved all 43 employees at Puskesmas Sumber Harum in 2024. The analysis showed no significant relationship between education (p-value 0.074) and knowledge (p-value 0.171). However, significant relationships were found for age (p-value 0.008), gender (p-value 0.006), training (p-value 0.019), attitude (p-value 0.009), and motivation (p-value0.037). Among these factors, attitude emerged as the most dominant with an OR of 17.452, contributing greatly to performance. Based on these findings, it is recommended that Puskesmas focus more on improving employee discipline and continue striving to enhance productivity and service quality.